The Case of the Inverted Male Wrestlers: Assessing Lyle Eslinger's Reversal of the Participants in Genesis 32:26-33. - MAKUJINA, JOHN (Catholic Biblical Quarterly, 2026)
A popular article by Lyle Eslinger makes a vigorous case for revising the common understanding of Jacob's wrestling match with the stranger at Penuel (Gen 32:23-33 [Eng. 32:22-32]). Eslinger proposes that Jacob was the one who struck his opponent in the ..., rather than vice versa. Notably, Eslinger's approach to the text is synchronic and thus a clear departure from previous source-critical attempts to accomplish the same thing (e.g., Hermann Gunkel). Consequently, he justifies his exchange of the participants in v. 26a with grammatical, literary, and exegetical arguments--all of which have yet to be addressed in academic literature. In thoroughly examining Eslinger's evidence, I have detected numerous deficiencies in his analysis. His conclusion, therefore, that Jacob struck the stranger in the ... lacks adequate support and does not merit serious consideration.